2019
DOI: 10.21273/hortsci14283-19
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits Fruit Softening by Regulating Ethylene Synthesis and Signaling Pathway in Tomato (Solanum lycopersicum)

Abstract: Hydrogen sulfide (H2S) has been proven to be a multifunctional signaling molecule in plants. In this study, we attempted to explore the effects of H2S on the climacteric fruit tomato during postharvest storage. H2S fumigation for 1 d was found to delay the peel color transition from green to red and decreased fruit firmness induced by ethylene. Further investigation showed that H2S fumigation downregulated the activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…H 2 S treatment could prolong the storage time of “ Red Fuji ” apple, and delay the ripening of apple fruit by suppressing the expression of ethylene synthesis-related genes ( MdACS1 , MdACS3 , MdACO1 and MdACO2 ) and signal transduction genes ( MdETR1 , MdERS1 , MdERS2 , MdERF3 , MdERF4 and MdERF5 ) (Zheng et al 2016 ). Similarly, H 2 S inhibits the expression of ethylene-related genes ( SlACO1 , SlACO3 , SlACO4 ; SlETR5 , SlETR6 , SlCRF2 , and SlERF2 ) in tomato (Hu et al 2019 ). Compared with the control, H 2 S treatment down-regulated the ethylene biosynthesis genes ( MaACS1 , MaACS2 , MaACO 1 and pectin lyase MaPL ), while up-regulated the ethylene receptor genes ( MaETR , MaERS1 and MaERS2 ) in banana fruit (Ge et al 2017 ).…”
Section: H 2 S Contributes To Plant Growth and Devmentioning
confidence: 99%
“…H 2 S treatment could prolong the storage time of “ Red Fuji ” apple, and delay the ripening of apple fruit by suppressing the expression of ethylene synthesis-related genes ( MdACS1 , MdACS3 , MdACO1 and MdACO2 ) and signal transduction genes ( MdETR1 , MdERS1 , MdERS2 , MdERF3 , MdERF4 and MdERF5 ) (Zheng et al 2016 ). Similarly, H 2 S inhibits the expression of ethylene-related genes ( SlACO1 , SlACO3 , SlACO4 ; SlETR5 , SlETR6 , SlCRF2 , and SlERF2 ) in tomato (Hu et al 2019 ). Compared with the control, H 2 S treatment down-regulated the ethylene biosynthesis genes ( MaACS1 , MaACS2 , MaACO 1 and pectin lyase MaPL ), while up-regulated the ethylene receptor genes ( MaETR , MaERS1 and MaERS2 ) in banana fruit (Ge et al 2017 ).…”
Section: H 2 S Contributes To Plant Growth and Devmentioning
confidence: 99%
“…One of the best-studied mechanisms to enhance fruit shelf life through H 2 S treatment is suppression of ethylene biosynthesis and signalling (Zheng et al 2016). H 2 S fumigation can delay the ripening and extend the fruit shelf life by reducing expression of ethylene biosynthesis genes ACS and ACO, ethylene receptor gene ETR1, ethylene response sensor 1 (ERS1) and ethylene response factors (ERFs) (Zheng et al 2016;Hu et al 2019).…”
Section: Impact Of H 2 S On Postharvest Qualitymentioning
confidence: 99%
“…In our recent studies, H 2 S was found to alleviate tomato fruit ripening by reducing ROS accumulation, and meanwhile ethylene biosynthesis and signaling pathway were inhibited by H 2 S (Yao et al, 2018;Hu et al, 2019). Though H 2 S has been found to be a senescence regulator in diverse fruits and vegetables, the mechanism of exogenous H 2 S in affecting the bioactive compounds of ethylene-induced tomato fruit ripening and senescence is still obscure.…”
Section: Introductionmentioning
confidence: 99%